2017
DOI: 10.1016/j.ijfoodmicro.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of different microenvironments and Lactobacillus sakei biotypes in Ventricina, a traditional fermented sausage from central Italy

Abstract: The present study evaluated the physico-chemical and microbiological features of Ventricina, considering for the first time the presence of different compartments deriving from the technology of production. In fact meat pieces (pork muscle and fat cut into cubes of about 10-20cm), mixed with other ingredients and then stuffed into pig bladder, are still distinguishable at the end of the ripening. They appear delimited on the outside by the casing and inside by thin layers consisting of spices (mainly red peppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 42 publications
8
23
0
Order By: Relevance
“…Generally, the lactobacilli strains do not present the same spectrum of action towards the pathogens (Table 3). No significant difference was found between the activity of lactobacilli isolated from camel milk and that isolated from mare's milk (JUMIII4), which supports researches of Tremonte et al (2017) who demonstrated that there is no relationship between the intensity of inhibition and the origin of inhibitory strains of Lb. plantarum.…”
Section: Antibacterial Activity Against Pathogenic Strainssupporting
confidence: 79%
“…Generally, the lactobacilli strains do not present the same spectrum of action towards the pathogens (Table 3). No significant difference was found between the activity of lactobacilli isolated from camel milk and that isolated from mare's milk (JUMIII4), which supports researches of Tremonte et al (2017) who demonstrated that there is no relationship between the intensity of inhibition and the origin of inhibitory strains of Lb. plantarum.…”
Section: Antibacterial Activity Against Pathogenic Strainssupporting
confidence: 79%
“…plantarum as starter in the MLF depends mainly on the strain used, whose metabolic activities are strongly linked to the ability to adapt to the main hurdles of wine (mainly high content of ethanol and low pH). As reported by several Authors (duToit et al, 2011; Tremonte et al, 2017) both ethanol and pH tolerance are strain-dependent features. So, in our study 42 Lb.…”
Section: Discussionmentioning
confidence: 52%
“…Statistical analyses were performed following the approach used by Tremonte et al (2017). In detail, kinetic parameters, microbial count levels and volume of protein bands were analyzed by a General Linear Model based on ANOVA (IBM SPSS Statistics 21).…”
Section: Methodsmentioning
confidence: 99%